SAARC: OPPORTUNITIES AND CHALLENGES - Kumar, Vinod (ShodhKosh: Journal of Visual and Performing Arts, 2022)
South Asian Association for Regional Cooperation is an organization that promotes regional cooperation and economic integration among South Asian countries. SAARC is an organization that brings together eight countries on one platform. Countries like Afghanistan, Bangladesh, Bhutan, India, Maldives, Nepal, Pakistan and Sri Lanka are its members. In the changing world scenario, the political and economic ambitions of the superpowers have systematically ended the immense possibilities of the rise of the global south. The proof of this is South Asia and the regional organization of these countries, SAARC. The present research paper throws light on its conceptual structure, opportunities, challenges and future prospects of this organization. Apart from this, it also throws light on the shared cultural and customs that present it as a well-organized southern unit despite the distinct national identity of these countries.